Osteonecrosis of the femoral head, nonunion and potential risk factors in Pauwels grade-3 femoral neck fractures: A retrospective cohort study. Issue 24 (June 2016) - Zhang, Yue-Lei; Chen, Song; Ai, Zi-Sheng; Gao, You-Shui; Mei, Jiong; Zhang, Chang-Qing
Abstract : Abstract: The present study was to analyze clinical outcome of Pauwels grade-3 femoral neck fractures treated by different surgical techniques. Potential risk factors associated with nonunion and osteonecrosis of the femoral head (ONFH) were investigated as well. The retrospective study comprised of 67 sequential patients treated between January 2008 and December 2011. Patients with Pauwels grade-3 femoral neck fractures were treated by operative reduction and internal fixation. Cannulated screws (CS) were used in 46 patients, dynamic hip screw plus CS (DHS+CS) in 14, and locking compression plate (LCP) for proximal femur in 7. Reduction quality was assessed according to Haidukewych criteria. Postoperative radiographic examinations were conducted to observe fracture healing. Fracture displacement, comminution, fashion of internal fixation, and the sliding effect were analyzed, regarding the incidence of nonunion and ONFH. All patients had a follow-up of 21.6 ± 6.0 months on average. The phenomenon of sliding effect was observed in 16 cases (23.9%). In terms of reduction quality, 64 cases were graded as excellent, 2 were good, and 1 was poor. ONFH was presented in 15 cases (22.4%) and nonunion was found in 8 (11.9%), with 1 patient had ONFH and nonunion concomitantly. Profound hip contour was preserved in 45 cases (67.2%). The fashion of internal fixation yielded different results regarding ONFH and nonunion, whereas the effects of fracture displacement, comminution, and the sliding effect were not significant. ONFH and nonunion were common complications following Pauwels grade-3 femoral neck fractures. Higher incidence of ONFH in DHS+CS and of nonunion in the LCP group should be noted.